The Interaction between Metabolic Disease and Ageing - Karan S. Rana; Helen R. Griffiths; Placido Navas; James E. Brown (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2014)
Two of the greatest crises that civilisation faces in the 21st century are the predicted rapid increases in the ageing population and levels of metabolic disorders such as obesity and type 2 diabetes. A growing amount of evidence now supports the notion that energy balance is a key determinant not only in metabolism but also in the process of cellular ageing. Much of genetic evidence for a metabolic activity-driven ageing process has come from model organisms such as worms and flies where inactivation of the insulin receptor signalling cascade prolongs lifespan. At its most simplistic, this poses a conundrum for ageing in humans - can reduced insulin receptor signalling really promote lifespan and does this relate to insulin resistance seen in ageing? In higher animals, caloric restriction studies have confirmed a longer lifespan when daily calorie intake is reduced to 60% of normal energy requirement. This suggests that for humans, it is energy excess which is a likely driver of metabolic ageing. Interventions that interfere with the metabolic fate of nutrients offer a potentially important target for delaying biological ageing.